2017
DOI: 10.1177/1534734617690949
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Polyhexanide/Betaine Gel Versus Silver Sulfadiazine for Partial-Thickness Burn Treatment

Abstract: Silver sulfadiazine is commonly used in the treatment of partial-thickness burns, but it sometimes forms pseudo-eschar and delays wound healing. Polyhexanide/betaine gel, a new wound cleansing and moisturizing product, has some advantages in removing biofilm and promotes wound healing. This study was designed to compare clinical efficacy of polyhexanide/betaine gel with silver sulfadiazine in partial-thickness burn treatment. From September 2013 to May 2015, 46 adult patients with partial-thickness burn ≥10% t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 22 publications
0
19
0
6
Order By: Relevance
“…In recent trials, topically applied silver-based compounds performed only equal or worse than non-silver based treatments. [21][22][23] Despite these few, rather unspecic metal-based treatments, the inorganic chemistry space is still largely ignored for antimicrobial applications. This is unfortunate because the tremendous variety of three-dimensional structural scaffolds available through metal coordination chemistry is an ideal starting point for the exploration of novel chemical space for new antibiotic compounds and provides a ready "escape from atland".…”
Section: Introductionmentioning
confidence: 99%
“…In recent trials, topically applied silver-based compounds performed only equal or worse than non-silver based treatments. [21][22][23] Despite these few, rather unspecic metal-based treatments, the inorganic chemistry space is still largely ignored for antimicrobial applications. This is unfortunate because the tremendous variety of three-dimensional structural scaffolds available through metal coordination chemistry is an ideal starting point for the exploration of novel chemical space for new antibiotic compounds and provides a ready "escape from atland".…”
Section: Introductionmentioning
confidence: 99%
“…It is extensively recognized as an organic osmolyte, and in plants serves as a protector against drought, high salinity and osmotic stress (Yancey et al, 1982). Betaine is particularly characterized by its lasting moisture-retentive ability and is widely used in skin care products due to its chemical structure featuring a hydrophilic head which attracts water molecules (Wattanaploy et al, 2017). Moreover, previous studies suggested that betaine helped improve the hydration state of the epithelium (Nicander et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Penelitian lain yang bertujuan untuk membandingkan efikasi klinis dari polyhexanide / betaine gel dengan perak sulfadiazine dalam perawatan luka bakar parsial menunjukkan hasil bahwa tidak ada perbedaan yang signifikan dalam waktu penyembuhan, tingkat infeksi, tingkat kolonisasi bakteri, dan biaya perawatan pada kedua kelompok. Skor rasa sakit kelompok gel polyhexanide / betaine secara sig-nifikan lebih rendah daripada kelompok perak sulfadiazine pada 4 sampai 9 hari setelah pengobatan dengan nilai P <0,001 (Wattanaploy, Chinaroonchai, Namviriyachote, & Muangman, 2017). Pada penelitian Akbar et al, 2013 dengan tujuan Untuk mengetahui efektivitas hydrogen peroksida sebagai pembersih luka dengan kolonisasi mikroba luka bakar kronik menunjukkan hasil bahwa Staphylococcus adalah yang paling sering mengisolasi kolonisasi bakteri pada pasien (59,2%) Rata-rata pengambilan pencangkokan kulit adalah 82,85% pada tungkai kanan, dan 65,61% di tangan kiri yang berbeda secara signifikan (P <0,05), Pemberian hidrogen peroksida intraoperatif aman dan secara signifikan meningkatkan rerata tingkat keberhasilan rata-rata pada luka kronis.…”
Section: Metodeunclassified